Maxims of Politeness by InterContinental LA Downtown Hotel in Responding One Star Reviews on Google Reviews - Celine Angelica Hermawan; Julia Eka Rini (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
The study explores Leech’s (1983) maxims of politeness in written feedback by Matthias Kaiser (MK) and David Valencia (DV) in responding to guests’ one star reviews at InterContinental LA Downtown Hotel. Using a qualitative method, the study analyzes how maxims of politeness are consistently applied despite differences in positions. The findings reveal that both MK, the Hotel Manager, and DV, the Director of Front Office, use all types of maxims of politeness, with approbation maxim being the most frequent, particularly in opening sentences to maintain the hotel’s image and expected guest relations. A combination of tact maxim and generosity maxim also appears frequently to address guests’ concerns while highlighting the hotel's efforts to improve. However, differences are identified in the ways MK and DV apply the same types of maxims of politeness through various sentences according to the main focus of their positions. They are also observed from the uses of different various and template sentences that both applied in their feedback. Differences clarify how MK’s is responsible for the hotel’s general operation, and DV is in charge of directly dealing with guests, showing maxims of politeness is crucial in the hospitality industry and influenced by high and low positions.